The Study of Inquiry Ability in the Photosynthesis Concept (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
The learning process has characteristics that reflect scientific, thematic, collaborative, and student-centered. This type of learning usually uses constructivist learning, and one of them is Inquiry. The inquiry is a process to get information by conducting observations or experiments to find answers or solve problems for questions or formulation a problem by using logical and critical thinking skills. This preliminary study focused on investigating new prospective teachersâ€™ inquiry ability. The respondents were new prospective teachers of Hamzanwadi University. The research instrument was a student worksheet with the topic â€œphotosynthesis.â€ Data analysis used descriptive statistical methods by calculating the score of each indicator of Inquiry after three assessments. Using of amount score to shows that for each indicator: (1) problem formulation (66), (2) Hypothesis (50), (3) Design (40), (4) Findings (12), and (5) Conclusions (10). It can be concluded that the new prospective teachersâ€™ in their involvement still needed to be trained, guidance, and continues to be developed. Therefore, Inquiry-based learning needs an extension for their next learning.